2023
DOI: 10.1127/entomologia/2023/2028
|View full text |Cite
|
Sign up to set email alerts
|

Mealybugs in Mediterranean persimmon: fruit infestation, seasonal trend and effect of climate change

Ángel Plata,
María A. Gómez-Martínez,
Francisco J. Beitia
et al.

Abstract: Mealybugs (Hemiptera: Pseudococcidae) are the main pest of persimmon in Spain, the second producer in the world. In order to develop an Integrated Pest Management (IPM) program, it is necessary to identify the main mealybug species, determine their phenology, and develop tools to predict damage. To do this, we sampled 17 orchards from the main persimmon producing area in Spain over two years. Pseudococcus longispinus (Targioni-Tozzeti) was the most abundant and widely distributed species. This mealybug species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The models showed that maintaining more than 10% ground cover by non-crop vegetation within the orchards and more than 15% of semi-natural habitats in the surrounding landscape can suppress P. longispinus by increasing its parasitism in persimmon. Although the economic injury levels of P. longispinus in persimmon have not yet been determined (Plata, Gómez-Martínez, et al, 2023a), these recommendations could significantly reduce mealybug abundance and fruit damage. However, long-term landscape planning remains a challenge, emphasizing the need for policymakers and stakeholders to optimize the management of invasive pests such as mealybugs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The models showed that maintaining more than 10% ground cover by non-crop vegetation within the orchards and more than 15% of semi-natural habitats in the surrounding landscape can suppress P. longispinus by increasing its parasitism in persimmon. Although the economic injury levels of P. longispinus in persimmon have not yet been determined (Plata, Gómez-Martínez, et al, 2023a), these recommendations could significantly reduce mealybug abundance and fruit damage. However, long-term landscape planning remains a challenge, emphasizing the need for policymakers and stakeholders to optimize the management of invasive pests such as mealybugs.…”
Section: Discussionmentioning
confidence: 99%
“…Nine alternate trees were selected per plot and sampled across the study (Figure S2). For each tree and sampling date, we counted and identified the mealybugs present in 120 leaves (30 per cardinal direction), 40 fruits (10 per cardinal direction) and the trunk surface (from ground level to 50 cm height) (Plata, Gómez-Martínez, et al, 2023a). All observed mealybugs were identified up to the species level using taxonomic keys (e.g.…”
Section: Sampling Designmentioning
confidence: 99%
See 2 more Smart Citations